Early Childhood Caries in 4- to 5-Year-Old Children in Erzurum, Turkey - Şengül, Fatih; Urvasızoğlu, Gelengül; Derelioǧlu, Sera; Seddik, Tarek; Çelikel, Periş; Baş, Aybike (Frontiers in Public Health, 2021)
Introduction: Early Childhood Caries (ECC) are tooth decays seen in children under 72 months old, associated with multiple predisposing factors and having a negative impact on the comfort of life. In this study, our aim was to assess the oral health conditions and ECC prevalence of children in the city of Erzurum, Turkey. Material and Methods: This cross-sectional epidemiological study was conducted in Ataturk University, Faculty of Dentistry, Pediatric Dentistry Department/Erzurum-Turkey, between 2015-2016. A total of 1156 preschool children (588 girls and 568 boys), with an age median of 4.9±0.3 (min 4, max 5) were included in the study. Restorative index (RI), deft, significant caries index (SiC), SiC10, treatment needs, number of lost primary teeth per 100 children, care index and prevalence of carious primary teeth were evaluated. Data were analyzed with Chi-square test and Mann-Whitney U test (p<0.05). Results: 73.3% prevalence of ECC was observed in the preschool children with a mean deft score of 3.9±4 and an increase in ECC with the age. We found restorative index as 2.2, SiC as 8.5, SiC10 as 12.3, caries treatment needs as 93.5%, care index as 2.1%, and number of lost primary teeth per 100 children as 0.9. Conclusion: High level of ECC revealed the necessity of starting an oral health educational program for mothers and dental screenings for children, and the demand for improving the oral and dental services.